The Relationship Between Exercise Types and the State of Mind of Rural Elderly Populations - Hongxia Tian, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Examining the nexus between exercise modalities and the cognitive-emotional status of elderly populations residing in rural locales is imperative for enhancing initiatives aimed at mental health enhancement and policy formulation. Consequently, this investigation delved into the correlation between exercise modalities and the psychological well-being of senior citizens in rural settings, while also scrutinizing variations in this association across gender and educational strata. Employing a self-administered questionnaire encompassing demographic particulars and physical activity data alongside a truncated version of the Profile of Mood States (POMS) scale, the study was conducted across six conveniently selected villages, encompassing a total of 346 participants post the exclusion of incomplete or invalid responses. Statistical analyses were executed utilizing SPSS 21.0 and Stata 12.0 software, employing multiple linear regression techniques to scrutinize the interplay between exercise modalities and psychological states. Furthermore, gender and educational attainment were utilized as stratifying variables to discern disparities in this nexus, also via multiple linear regression modelling. The research unveiled that elderly individual engaging in intermittent exercise regimens exhibited diminished fatigue levels. Moreover, gender and educational attainment exhibited divergent impacts on this relationship, with female elderly participants partaking in intermittent exercise reporting reduced energy and anxiety levels, while heightened educational levels correlated with diminished depression and anxiety scores among those engaged in intermittent exercise, in comparison to counterparts adhering to continuous exercise routines. These findings bridge a lacuna in existing literature concerning exercise modalities, offering insights pivotal for policy development in this domain.